Nanocompósitos semicondutores ZnO/TiO2 e testes fotocatalíticos - Shirley Santana Silva (2009)
Titanium dioxide is an efficient photocatalyst, but it is possible to improve its efficiency with better charge separation by coupling TiO2 with other semiconductors. To achieve this, in these work nanometric particles of ZnO were used to impregnate TiO2 P25. Zinc acetate was used as molecular precursor for ZnO. The preparation of ZnO/TiO2 semiconductors composites was performed by impregnating zinc acetate di-hydrate on to the surface of TiO2 P25, followed by thermal treatment. ZnO/TiO2 composites were obtained at different molar proportions (20, 10, 7, 5, 3 and 1%). ZnO is also a good photocatalyst it was obtained by pyrolysis of zinc acetate di-hydrate under the same experimental conditions of the composites. ZnO as well as ZnO/TiO2 composites were characterized by X-ray diffraction (XRD), micro-Raman spectroscopy, difuse reflectance spectroscopy, measurement of surface area (BET) and scanning electron microscopy (SEM). Raman spectroscopy data revealed an interaction between ZnO and TiO2 that was observed by an enlargement of TiO2 peaks and a change on the rate relation between anatase and rutile phases on the composites. The size of ZnO particles, measured by XRD, was 21.2 nm and for ZnO/TiO2 20% composite was 17.2 nm. A new Raman band at 801 cm-1 was observed which was assigned to the presence of nanosized materials. The BET analysis revealed that both ZnO and composites are mesoporous materials. hotodegradation of Drimaren Red azo-dye revealed better efficiency for ZnO/TiO2 3% nanocomposite and for ZnO pure when compared with TiO2 alone and other ZnO/TiO2 molar proportions. Other azo-dyes such as Congo Red and Janus Green were tested but these dyes adsorbed strongly the catalysts powders, therefore it was not possible to test the photo-degradation for these dyes.